Understanding Community Participation within Sustainable Rural Tourism Development (A Single Case Study in Kalibiru Village, Yogyakarta Special Region, Indonesia) - Anggraheni, Yulita (Jurnal Ilmiah Administrasi Publik, 2018)
The development of rural tourism is estimated can led to a new dimension of sustainable development. The government of Indonesia has made some efforts to realize the target of increasing the countrys foreign exchange income with digital tourism, rural tourism homestay, and air connectivity. Regarding this target, community participation is needed to become the main subject of rural tourism. However, the development of rural tourism in Indonesia still encounters various obstacles such as lack of promotion and innovation in programs. Using qualitative method, author explore the barriers, facilitators and how to overcome challenges within the sustainable rural tourism development in Kalibiru village, Yogyakarta Special Region, Indonesia.